Newly onset cytopenias not always indicate a relapsing AML after allogeneic HSCT, a case of non-destructive post transplant lymphoproliferative disorder - Süreyya Yiğit Kaya; Abdullah Emre Askin; Sebnem Bektas; Aslı Çakır; Ömür Gökmen Sevindik (Leukemia Research Reports, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains an effective option for the treatment of intermediate and high-risk Acute myeloid leukemia (AML). Post-transplant lymphoproliferative disorder (PTLD) is related to the intensity of post-transplant immunosuppression. Although Epstein-Barr virus (EBV) seropositivity and reactivation can be a major risk factor for PTLD. A few PTLDs could be EBV negative. There are a very limited number of PTLD cases following HSCT in patients with AML. We present a differential diagnosis of cytopenias after allo-HSCT. This is the first report of an AML patient developing bone marrow EBV-negative PTLD relatively late in their post-transplant course.